Usefulness of MRI in takotsubo cardiomyopathy: a review of the literature - Kohan, Andres Alejandro; Yeyati, Ezequiel Levy; De Stefano, Luciano; Dragonetti, Laura; Pietrani, Marcelo; de Arenaza, Diego Perez; Belziti, Cesar; García-Mónaco, Ricardo Daniel (Cardiovascular Diagnosis and Therapy, 2014)
Takotsubo cardiomyopathy (TC) is a disease that can be misinterpreted as a more serious acute coronary syndrome. Its clinical characteristics resemble those of a myocardial infarct, while its imaging characteristics are critical on correctly characterizing and diagnosing the disease. From angiography, where coronary anatomy is evaluated, to cardiac magnetic resonance (CMR), where morphology and tissue characterization is assessed, the array of imaging options is quite extent. In particular, CMR has achieved great improvements (stronger magnetic fields, better coils, etc.) in the last decade which in turn has made this imaging technology more attractive in the evaluation and diagnosis of TC. With its superior soft tissue resolution and dynamic imaging capabilities, CMR is currently, perhaps, the most useful imaging technique in TC as apical ballooning or medio-basal wall motion abnormalities (WMA), presence of wall edema and late gadolinium enhancement (LGE) characteristics are critical in the diagnosis and characterization of this pathology. In this review, CMRs role in TC will be evaluated in light of the current available evidence in medical literature, while also revising the clinical and physiopathologic characteristics of TC.